2008
DOI: 10.1016/j.jad.2008.01.008
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of specific positive future expectancies and global hopelessness as predictors of suicidal ideation in a prospective study of repeat self-harmers

Abstract: Method. One hundred and forty four adults hospitalized following a suicidal self-harm episode completed a range of clinical and psychological measures in hospital and were followed up approximately 2.5 months after discharge. All participants reported at least one other self-harm episode in addition to the index episode.Results. Hierarchical regression analyses confirmed that specific positive future expectancies were better predictors of Time 2 suicidal ideation than global hopelessness.In addition, as hypoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
52
1
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(61 citation statements)
references
References 44 publications
7
52
1
1
Order By: Relevance
“…Previous research has also shown that it is a better predictor of future suicidal ideation than BHS (O'Connor et al, 2008). Therefore it may be a useful tool in the assessment of hopelessness in this population.…”
Section: The Relationship Between Self-reported Hopelessness and Posimentioning
confidence: 93%
See 1 more Smart Citation
“…Previous research has also shown that it is a better predictor of future suicidal ideation than BHS (O'Connor et al, 2008). Therefore it may be a useful tool in the assessment of hopelessness in this population.…”
Section: The Relationship Between Self-reported Hopelessness and Posimentioning
confidence: 93%
“…However, studies of the correlation between self-reported hopelessness and suicidal ideation have shown a large effect size (Kao et al, 2012;O'Connor et al, 2008). To achieve 80% power to detect a large correlation at an alpha level of 5%, a sample size of 29 within the psychosis group was needed.…”
Section: Power Calculationmentioning
confidence: 99%
“…Positive emotions in suicidal patients have been linked to improved problem-solving [17], and a study of patients hospitalized for self-harm found that low positive future orientation more strongly predicted recurrent selfharm after discharge than did global hopelessness [18]. Therefore, explicit targeting of positive cognitive and emotional states like gratitude and positive future orientation may have effects on suicide risk above and beyond standard approaches.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, low levels of positive future thinking, rather than the preponderance of negative future thinking, were a better predictor of suicidal ideation than hopelessness, in patients who had attempted suicide [22,23]. Additionally, suicidal ideation were significantly higher 2.5 months after a suicide attempt among persons who reported difficulties to reengage in new goals when those they were pursuing were unobtainable [24].…”
Section: Introductionmentioning
confidence: 92%
“…Helping people who lost interest in life engage in new personal projects that offer meaning to their life could be an innovative prevention strategy [23,24,25,26]. This is especially important in old age when illnesses or disability make goals unattainable, and consequently increase the wish to die and suicidal ideation [27,28].…”
Section: Introductionmentioning
confidence: 99%